Evaluation of Candidal Carriage Among Smokers and Non-Smokers - Umar Irfan; Salik Rasool; Perveen Memon; Shazia Irum; Bushra Jabeen; Faraz Khan (Journal of Bahria University Medical and Dental College, 2021)
Objectives: To determine the Candidal carriage among smokers and non-smokers and with different intra-oral sites including examination of various biotypes of Candida. Study design and setting: Cross-sectional based study conducted at Dr. Ishrat ul Ebad Khan Institute of Oral Health Sciences and Dow International Dental College, Karachi, from May 2017 till April 2018. Methodology: Comprised 100 patients (50 smokers and 50 nonsmokers) between 20 and 60 years of age. The collection was performed through sterile cotton swab to evaluate oral Candidal carriage and the colonizing Candida species using Sabouraud Dextrose Agar (SDA) and API20C AUX (BIOMERIEUX). Data was analyzed Spss version 20. Results: A total of 100 participants (50 smokers and 50 non-smokers) were evaluated for candidal carriage. The common age group was 20-30 years in both the groups, without significant difference (p-value 0.79). Frequency of candidal carriage was comparable among smokers 14 (28.0%) to non-smokers 10 (20.0%), with a statistically insignificant p-value 0.35. Based on various biotypes among smokers and non-smokers, Candida albicans was 9(18%) and 7(14%), Candida glabrata was 4(8%) and 2(4%); and Candida tropicallis was 1(2%) each for both smokers and non smokers. Dorsum of tongue harbored all prevalent biotypes i.e. Candida albicans, Candida glabrata and Candida tropicalis as statistically significant among smokers (p-value 0.04). Conclusion: Candidal carriage was comparable among smokers and non-smokers. Candida albicans and Candida glabrata were the common biotypes predominantly among smokers.